THE EFFECT OF ORAL CARE INTERVENTION ON ORAL HEALTH STATUS OF INTUBATED PATIENTS IN THE INTENSIVE CARE UNIT - Diah Tika Anggraeni; Ayu Trisna Hayati; Aan Nur'aeni (Belitung Raya Foundation, Indonesia, 2020)
Background: Oral infections can be a potential source of infection resulting in a variety of systemic diseases, especially in intubated patients in an Intensive Care Unit (ICU). Endotracheal tube (ETT) of the intubated patient’s mouth can be an entry point and place of bacteria colonization that causes ventilator-associated pneumonia which is one of the causes of the patient’s death in ICU. Nurses as caregivers have an important role in providing oral care intervention to maintain oral health and prevent the infection. Objective: This study aimed to analyze the effect of oral care intervention on oral health status of intubated patients in the ICU. Methods: This was a pre-experimental study with one group pre-test post-test design. A consecutive sampling was used to select 18 intubated patients in the ICU of Al Islam hospital in Bandung. Oral health status was evaluated by Beck Oral Assessment Scale (BOAS). Descriptive analysis was used for the univariate analysis and t-test was used for bivariate analysis. Results: The results showed that oral health scores before and after intervention were 11.94 and 13.28 (p=.004). The BOAS subscales had a significant worsening of the lips, gingiva, oral mucosa and saliva (p<.05), while there was an improvement in teeth subscale after oral care intervention (p<.001). Conclusion: The results suggested that the oral health status of intubated patients had worsened, despite routinely oral care intervention using chlorhexidine gluconate. Mucosa care may become an essential part of the oral care intervention for intubated patients. Therefore, additional topical agent is needed to maintain the moisture of the mucosal membrane, so that the oral health status of intubated patients will be better.